Workaholism - Indications for diagnosis and review of interventions - Diana Malinowska; Sabina Staszczyk; Aleksandra Tokarz (Nofer Institute of Occupational Medicine, 2015)
Due to numerous psychological and health costs, the issue of workaholism requires taking appropriate actions by relevant specialists, including occupational medicine services. This paper presents the criteria and indicators used to diagnose this phenomenon, as well as the review of literature that discusses interventions aimed at preventing workaholism and reducing risk factors, workaholism detection and treatment. The review included 17 scientific publications from the science database Academic Search Complete, which met the basic criterion: the presentation of an intervention aimed directly at reducing workaholism/work addiction, not its side effects. The results of the review indicate a variety of potential actions, including individual, family and organization, which can be directly used in the practice of occupational medicine services (doctors and inspectors of working conditions). In addition, the review can be used as a reference material for other users, such as therapists, coaches, trainers, and human resources (HR) professionals. The article discusses the problem of the important role of occupational medicine services in both the diagnosis and the inhibition of workaholism development. It also presents guidelines how to conduct and analyse the effectiveness of interventions. Med Pr 2015;66(1):71-83